Determinants of Financial Performance in Indonesia’s Renewable Energy Sector: The Interplay of Green Financing, Capital Expenditure, and Leverage - Alwani; Rosmini Ramli (Indonesian Scientific Publication, 2026)
This research investigates how green bonds, green investment, capital expenditure, and leverage influence the financial performance of renewable energy firms listed on the Indonesia Stock Exchange between 2022 and 2024. The study is driven by the escalating challenge of global climate change, where the energy sector remains the largest source of greenhouse gas emissions. This situation has accelerated the transition toward renewable energy, accompanied by a consistent decline in return on assets among renewable energy companies. The novelty of this work lies in its simultaneous examination of four financial and sustainability variables within a single empirical framework applied to Indonesia’s renewable energy industry. The sample comprises 21 renewable energy firms selected through purposive sampling based on continuous listing status, availability of complete financial data, and sustainability disclosure during the observation period, observed over a three-year period. A quantitative method was employed, with panel data regression analysis conducted using EViews 13. The results of partial testing reveal that both green bonds and leverage exert a negative impact on financial performance, while green investment and capital expenditure show no significant effect. These findings underscore the short-term financial considerations associated with green financing and capital structure decisions during the energy transition, and offer empirical insights into the short-term financial implications of green financing and capital structure decisions in Indonesia’s renewable energy sector.